(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, the concentration of abrasive particles accumulated in the crankcase of the transmission block under high ambient temperature conditions in the transmission blocks depends on the crankcase sealing and the recorded refueling frequency